A novel exfoliated manganese phosphoselenide as a high-performance anode material for lithium ions storage - Shen, Hailin; Zhang, Wei; Zhang, Yuheng; Wang, Wei; Wang, Min; Liu, Tianyu (Frontiers in Chemistry, 2022)
Layered manganese phosphoselenide(MnPSe3) is expected to be a potential anode for Li ions storage due to it combines the merits of phosphorus with metal selenide. It promotes charge transfer and ensures the high theoretical capacity up to 746 mA h g-1. In this work, a comprehensive study clearly demonstrated that bulk MnPSe3 electrode is inability to maintain the integrity of structure with severe detectable fracture or pulverization after full lithiation/delithiation, resulting in poor rate capability and cycling stability. Additionally, exfoliated few-layered MnPSe3 nanoflakes by the ultrasonic method show the enhanced electrical conductivity and resistance to volume expansion. It has a high initial discharge/charge capacity reaching to 524/796 mA h g-1 and outstanding cycling stability with the charge capacities of 709 mA h g-1 after 100 cycles at 0.2 A g-1 within the potential window of 0.005-3 V vs. Li+/Li. While further improving the cycles, the retention rate was still held ∼72% after 350 cycles. This work provides the new insights into exploiting new novel layered materials, such as MnPSe3 as anodes for lithium ion batteries.